E-Catalog Application Development for Public Facility using Website Usability Evaluation Tool - Sri Lestari; Hendra Dea Arifin; Muhammad Dzulfikar Fauzi; Agung Fatwanto (Faculty of Science and Technology, UIN Sunan Kalijaga Yogyakarta, 2014)
The interaction between user and computer is a factor that should be considered in building a website. Most users often judge a system's interface, instead of the function. A good website should ideally have the ease of use (usability) that makes users easier access to the information presented. But in fact, the lack of reusability factor to be considered in designing a website. Bad user interface design is usually a reason for not using an application or software. In addition, bad user interface could make a fatal mistake. The design should be user-centered. Therefore, there is an evaluation process conducted by users on the design results. Webuse (Website Usability Evaluation Tool) is a method that can help a web developer or web designer know the level of usability not only in terms of design but also in terms of content organization, navigation and link, and performance and effectiveness. We build an e-catalog of public facilities in the city of Yogyakarta by applying the Webuse concept. Result shows that these public facilities have good usability level.